Ministers on Salvation: Soteriological Views of Pioneers and Pastors in the Protestant Church in the Netherlands - Paas, Stefan (Journal of empirical theology, 2023)
Missiology has always been inspired by soteriology, that is, Christian views of salvation. However, little is known about the actual soteriological beliefs of missionary practitioners. This article is an explorative qualitative study of soteriological beliefs among Dutch Protestant ministers who work in pioneer settings (N=20) and established churches (N=40). Our research shows that, contrary to what might be expected, these two groups (termed ‘pioneers’ and ‘pastors’) are very much alike with regard to their soteriological beliefs. The majority are convinced of the uniqueness of Jesus, and the connection of salvation with God and/or Jesus – even if this salvation is often expressed in immanent terms. Only two differences have been found between pastors and pioneers. Pioneers experience more challenges in communicating the uniqueness of Christianity and they are more likely to have traditional views of ‘eternal lostness’.